Analisis Faktor Yang Mempengaruhi Minat Belajar Materi Agama Islam Pada Kelas V di SDN 054903 UPL.Kayu Balok - Lia Syahfitri; Yunizar Ritonga; Dhevy Kartika Ayu Angkat; Naila Audiva Hutasuhut; Annio Indah Lestari Nasution (Universitas Veteran Bangun Nusantara, 2024)
This research aims to analyze the factors that influence students' interest in learning about Islamic Religious Education in class V at SDN 054903 UPL K. Balok. Islamic religious education has an important role in shaping the character and values of Muslim society in Indonesia. However, students interest in learning is often not optimal, influenced by teaching methods, relevance of material, parental support, and school environmental conditions. Using a qualitative approach, this research collects data through interviews, observation and documentation. The research results show that students' interest in learning is influenced by internal factors, such as physical and psychological conditions, as well as external factors, such as the environment and social support. This research provides recommendations for improving teaching methods, increasing family support, and creating a conducive learning environment to increase students' interest in learning.